Dynamic behavior of the nucleus pulposus within the intervertebral disc loading: a systematic review and meta-analysis exploring the concept of dynamic disc model - Deneuville, Jean-Philippe; Billot, Maxime; Cervantes, Alexandra; Peterlongo, Sylvain; Meyer, Martin; Kolder, Mezika; Escande, Marie; Bourgeois, Mathilde; Pallot, Adrien; David, Romain; Roulaud, Manuel; Ounajim, Amine; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe dynamic disc model (DDM) is a theoretical framework in spine mechanics that theorizes the behavior of the nucleus pulposus within the intervertebral disc under various loads. The model predicts displacement of the nucleus pulposus away from the bending loads, for example backward displacement of the nucleus pulposus with a flexion load. These predictions are regularly used as a theoretical basis for explaining certain disc pathologies, such as disc herniation.MethodsWe screened seven databases (CENTRAL, Embase, MEDLINE, CINAHL, ScienceDirect, Google Scholar, and HAL) up to July 2024, identifying studies through a PRISMA-guided approach that detailed the mechanical transformation (displacement and deformation) of the nucleus pulposus under bending load on the intervertebral disc. We conducted a double-blind data extraction and quality assessment of the body of evidence. Finally, we performed a meta-analysis of proportions.ResultsFrom the 9,269 articles screened, 14 studies were included in the systematic review and meta-analysis. Magnetic Resonance Imaging (MRI) was employed in 92.8% of the studies, revealing four strategies for assessing nucleus pulposus transformation. The meta-analysis of asymptomatic subjects’ data demonstrated that the nucleus pulposus behavior aligned with dynamic disc model predictions in 85.4% (95% CI = [79.4–91.4]) across spinal regions and bending directions. However, significant heterogeneity and low study quality were noted. Only one study used discography to assess the DDM in a discogenic pain population, identifying discrepancies in nucleus pulposus transformation and contrast agent leakage.ConclusionEvidence for the dynamic disc model for intact discs is of low strength, whereas very limited evidence challenges the dynamic disc model for fissured discs. New multiparametric MRI studies may help guiding future clinical assessment protocols.Systematic Review RegistrationCRD42022331774.